Between Algorithm and Adat: How Bugis-Makassar MSMEs Negotiate AI Marketing Through the Lens of Siri' na Pacce - Hery Maulana Arif; Wiwin Riski Windarsari (Economics and Business Journal (ECBIS), 2026)
The rapid proliferation of AI-powered marketing technologies in emerging markets poses a fundamental challenge to culturally-grounded micro, small, and medium enterprises (MSMEs): how can algorithmic imperatives be reconciled with indigenous value systems that define not only business practice but collective identity? Despite growing research on both AI adoption in SMEs and indigenous knowledge preservation, scholarship rarely examines how traditional values actively mediate rather than merely moderate commercial technology adoption. This study addresses that gap by investigating how MSMEs in Makassar City, Indonesia, negotiate AI marketing integration while preserving siri’ na pacce, the Bugis-Makassar philosophical framework centred on dignity (siri’) and solidarity (pacce). Employing interpretive phenomenology integrated with Community-Based Participatory Research (CBPR), the study conducted 23 in-depth interviews and three focus group discussions with 44 MSME owners and key personnel across traditional culinary, artisan craft, ethnic fashion, and digital service sectors. Template analysis generated four overarching themes: (1) value-based technology discernment, wherein siri’ na pacce operates as an active epistemological filter for evaluating AI tools; (2) strategic selective adoption, wherein enterprises accept algorithmically aligned functions while rejecting culturally incompatible features; (3) cultural indigenization of technology, wherein AI systems are actively reoriented toward communal rather than individualistic ends; and (4) constrained agency under platform power, wherein algorithmic visibility systems penalise cultural non-conformity with market exclusion. These findings challenge technological determinism and advance decolonial computing theory by demonstrating that indigenous values simultaneously enable epistemological agency and are constrained by structural power asymmetries, a duality insufficiently theorised in prior technology adoption frameworks. The study calls for regulatory frameworks establishing indigenous data sovereignty, participatory AI co-design with local communities, and cooperative digital infrastructure as conditions for authentic, rather than performative, cultural integration.